Management Of Large Radicular Cyst by Root End Resection - Mohamed G, Ramies; Das, Sambarta; Panda, Swagat; Agnihotri, Namratha Lakshmi; Agnihotri, Yoshaskam; Satapathy, Eleena (Journal of Neonatal Surgery, 2025)
A 45-year-old male patient who reported to the department with a chief complaint of pain, tenderness and swelling in upper front tooth region showed a soft, non-tender, non-fluctuant swelling on examination, between teeth #11 #12 and #13 with radiographic evidence of periapical radiolucency. Cone Beam Computed Tomography (CBCT) scans confirmed a well-defined radiolucency in the affected region, indicative of a Radicular cyst. Root Canal Treatment was completed with Bio-ceramic sealer obturation during the third visit. An Endodontic Surgery was performed to remove the cystic content, followed by retrograde filling and the placement of bone graft material, a platelet-rich fibrin (PRF) membrane, and sutures to facilitate bone regeneration. This comprehensive approach aimed to resolve the periapical pathology and promote tissue healing around the affected tooth.